Tailoring gellan gum spongy-like hydrogels’ microstructure by controlling freezing parameters - Moreira, Helena R. (2020)
The following are available online at http://www.mdpi.com/2073-4360/12/2/329/s1, Figure S1: Freezing profiles of 0.75% GG hydrogels, Figure S2: Effect of freezing conditions (standard method, NFD, and IFD at −20, −80, and −210 ◦C) over the properties of 0.75% GG dried polymeric structures and spongy-like hydrogels., Figure S3: Water uptake of 1.25% GG spongy-like hydrogels at −20, −80, and −210 ◦C using different freezing systems, Figure S4: Scaffolds reproducibility, Figure S5: Effect of freezing conditions (standard method, NFD, and IFD at −20, −80, and −210 ◦C) over hDFb behavior in 0.75% GG spongy-like hydrogels.